Vectors of technical innovation delivery by small and medium Australian construction firms (Construction Economics and Building, 2016)
Long-established Schumpeterian theory on innovation assumes that significant innovations are generated by large companies with ample spare resources. The allocation of time and money to speculative endeavours with unclear outcomes has often been regarded as beyond the scope of small and medium-sized enterprises (SMEs). As a result, authorities sometimes advise SMEs to concentrate on the adoption of existing innovative products and processes rather than the generation of new creative ideas. Despite this traditional wisdom, some very capable individuals actively choose to participate in the SME sector because the relative absence of internal bureaucratic processes and the capacity for agile response to changing circumstances. Ten case studies of significant technical innovations generated within construction SMEs were examined in the light of common themes identified through a literature review. The case studies were classified according to existing taxonomies of innovation. Content analysis was used to map the identified themes against the published material about the innovations from patent applications, company websites, trade literature and industry magazines. The findings indicate that SME innovation stems from several distinct motivations. These drivers of innovation can be described vectors. They inspire innovative solutions but the generated innovations also drive development towards solutions for other, quite different problems.